Risk Factors and Diagnosis of Advanced Cutaneous Squamous Cell Carcinoma - Brancaccio, Gabriella; Fargnoli, Maria Concetta; Briatico, Giulia; Pellegrini, Cristina; Rocco, Tea; Moscarella, Elvira (Dermatology Practical & Conceptual, 2021)
Cutaneous squamous cell carcinoma (cSCC) is the second most common cancer affecting humans. The combination of the increasing incidence and high mortality in advanced stages of the disease, defines cSCC as an emerging public health problem. Advanced disease includes metastatic and locally advanced cSCC. Metastatic disease refers to the presence of locoregional metastasis (in transit or to regional lymph nodes) or distant metastasis. Locally advanced disease has been defined as non-metastatic cSCC that is unlikely to be cured with surgery, radiotherapy, or combination treatment. While metastatic cSCC is easily diagnosed, locally advanced disease lacks consensus definition and diagnosis is made after multidisciplinary board consultation. Identifying patients with aggressive cSCC at highest risk for relapse may prevent the occurrence of advanced disease. Prognostic factors suggested by most guidelines include tumor diameter (>2 cm), localization on temple/ear/lip/area, thickness (>6 mm), or invasion beyond subcutaneous fat, poor grade of differentiation, desmoplasia, perineural invasion, bone erosion, immunosuppression, undefined borders, recurrence, growth rate, site of prior radiotherapy, and lymphatic or vascular involvement. Although risk factors associated with worse outcomes are well known, there is still a gap of knowledge on the precise risk of each factor taken individually. The aim of this review is to summarize cSCC prognostic factors and encompass the various staging systems to guide management and follow-up in cSCC patients at higher risk for local recurrence and metastasis. Finally, we describe the hallmarks of the advanced disease. Advanced cSCC diagnosis should be made by a multidisciplinary board considering patients’ performance status and disease characteristics